2013
DOI: 10.3109/01480545.2013.851692
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity evaluation of HMG CoA reductase inhibitor rosuvastatin

Abstract: The genotoxic potential of rosuvastatin as one of the statin drugs was assessed by chromosomal aberrations (CAs), micronucleus (MN) and DNA damage by comet assay in the human peripheral blood lymphocytes. Rosuvastatin was used at concentrations of 0.0625, 0.125, 0.25, 0.5 and 1 µg/mL for these in vitro assays. In all assays, a negative and positive control were also included. CA frequencies were significantly increased in all concentrations at 24 hours and significantly increased in all concentrations except 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…But the results of these studies are contradictory; it was found that atorvastatin significantly decreased MN frequency induced by ionizing radiation in human lymphocytes, 29 while rosuvastatin significantly increased MN frequency at all concentrations in human lymphocytes. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the results of these studies are contradictory; it was found that atorvastatin significantly decreased MN frequency induced by ionizing radiation in human lymphocytes, 29 while rosuvastatin significantly increased MN frequency at all concentrations in human lymphocytes. 30…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an in vitro study had shown that rosuvastatin decreased the cytokinesis-block proliferation indices in human peripheral blood lymphocytes, but this effect was not statistically significant. 30…”
Section: Discussionmentioning
confidence: 99%
“…It is worthmentioning that statins may have an influence on genomic damage (Pernice et al, 2006). Some types of statins such as rosuvastatin can be considered cytotoxic in human peripheral lymphocytes (Berber et al, 2014) since it may increase the chromosomal aberration frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Berber et al (2014) showed that rosuvastatin presented genotoxic effects based on results obtained through the evaluation of chromosomal aberrations, micronuclei and damage to DNA (comet assay). These results should be considered, especially since they were observed in human peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 99%